2005
DOI: 10.4049/jimmunol.175.11.7170
|View full text |Cite
|
Sign up to set email alerts
|

An Hour after Immunization Peritoneal B-1 Cells Are Activated to Migrate to Lymphoid Organs Where within 1 Day They Produce IgM Antibodies That Initiate Elicitation of Contact Sensitivity

Abstract: Elicitation of contact sensitivity (CS), a classic example of T cell-mediated immunity, requires Ag-specific IgM Abs to trigger an initiation process. This early process leads to local recruitment of CS-effector T cells after secondary Ag challenge. These Abs are produced by the B-1 subset of B cells within 1 day after primary skin immunization. In this study we report the surprising observation that B-1 cells in the peritoneal cavity are activated as early as 1 h after naive mice are painted with a contact-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 31 publications
4
73
0
1
Order By: Relevance
“…Based on evidence presented here and in our previous studies (3), we know that cells in the PerC, like B-1 cells, express CD11b. Although it is clear that CD5 expression can be used to enrich for PerC cells with initiator activity, it may not define the population because we previously found that transfer of either CD5 ϩ or CD5 Ϫ CD11b ϩ PerC cells could transfer initiation (1,3). CD5 expression may be induced or further up-regulated on initiator B cells activated by sensitization, as all B cells are capable of expressing CD5 when activated (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on evidence presented here and in our previous studies (3), we know that cells in the PerC, like B-1 cells, express CD11b. Although it is clear that CD5 expression can be used to enrich for PerC cells with initiator activity, it may not define the population because we previously found that transfer of either CD5 ϩ or CD5 Ϫ CD11b ϩ PerC cells could transfer initiation (1,3). CD5 expression may be induced or further up-regulated on initiator B cells activated by sensitization, as all B cells are capable of expressing CD5 when activated (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…These Abs enter the circulation and, upon local challenge to the skin, induce a mild, local vasoactive response that peaks 2 h after challenge (7,8). Evidence suggests that this early response is required to recruit rare Agspecific T cells to the local site of exposure, since interference with any step in this pathway or with mechanisms of T cell recruitment within the 2-h window postchallenge, effectively prevents the subsequent development of the severe, delayed inflammatory response (3,4,9). For this reason, the mechanisms responsible for the early response have been termed DTH or CS initiation.…”
Section: Identification Of Initiator B Cells a Novel Subset Of Activmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a clear influence of the spleen on peritoneal B-1a cells is known. Splenectomy results in a severe loss of peritoneal B-1a cells [8,9] and more recently, it has been demonstrated that upon appropriate antigen challenge specific peritoneal B-1a cells quickly migrate to the spleen [23].…”
Section: Discussionmentioning
confidence: 99%